Developing a career promotion model for Romanian football referees - Antonie, Andrei (2010)
Football refereeing has become more demanding in terms of physical and mental preparation. Elite football referees are seen as athletes nowadays and the latest changes have brought major challenges in terms of job and occupation. The officials have changed their perspectives regarding their sport involvement due to the national football associations which have decided to have a certain number of professional referees. Therefore, top level football referees have taken the path towards professionalization.